L’accès à l’eau potable et à l’assainissement dans les villes des pays en développement : cas de Basoussam (Cameroun) - Mpakam Hernanie Grelle; Kamgang Kabeyne; B.V.; Kouam Kenmogne; G.-R.; Tamo Tatietse; Georges E. Ekodeck (VertigO)
Bafoussam like many cities of developing countries, has not stopped spreading. Its population is more and more increasing, precarious quarters too. The population’s need of water is increasing. In Cameroon, the National Water Corporation (SNEC) is more and more unable to respond to the population’s need. The state’s passivity and extreme poverty have led to the implementation of decentralised units such as wells, rivers, streams for basic needs. The inefficiency of units in charge of collecting dirt, the absence of recycling units and the prevalence of cesspools expose the decentralised units to pollution. The sewer system does not exist. Consequently, people drink unsafe water to the detriment of their health. The situation is well-known in many cities of developing countries. This paper aims at presenting the problem in its whole context thanks to a detailed study of some precarious quarters of the city of Bafoussam. It also aims at highlighting problems which are linked to the access of potable water and at suggesting solutions for a resource management while taking into consideration the local means and social context.